2014
DOI: 10.1021/cm4031057
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Gallium Sulfide Films Using Hexakis(dimethylamido)digallium and Hydrogen Sulfide

Abstract: Gallium sulfide (GaS x ) was synthesized for the first time via atomic layer deposition (ALD), using hexakis(dimethylamido)digallium and hydrogen sulfide. The growth characteristics and surface reaction mechanism for the GaS x ALD were investigated using in situ quartz crystal microbalance, quadrupole mass spectrometry, and Fourier transform infrared spectroscopy measurements. The as-deposited films were analyzed for their surface morphology, elemental stoichiometry, chemical states and stability, and crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
100
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 74 publications
13
100
1
Order By: Relevance
“…For many ALD oxide processes, hydroxyl (OH) groups are the major reactive sites, [62] whereas the analogous thiol (SH) groups can play an important role for sulfides. As an example, Meng et al [63] found a rapid decrease in the density of thiol groups, and, consequently, in the ALD growth rate of GaS x deposited from Ga 2 (NMe 2 ) 6 and H 2 S, when increasing the deposition temperature from 125 to 225 °C.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…For many ALD oxide processes, hydroxyl (OH) groups are the major reactive sites, [62] whereas the analogous thiol (SH) groups can play an important role for sulfides. As an example, Meng et al [63] found a rapid decrease in the density of thiol groups, and, consequently, in the ALD growth rate of GaS x deposited from Ga 2 (NMe 2 ) 6 and H 2 S, when increasing the deposition temperature from 125 to 225 °C.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…It was previouslys hown that the presence of gallium is crucial for the sufficient solubility of raree arth ions in amorphous chalcogenides, which is generally low in typical binary compositions (As/S, As/Se, Ge/S, Ge/Se,e tc.). [9] Recently,G aS x films were prepared by atomic layer deposition (ALD) by using Ga 2 (NMe 2 ) 6 and H 2 S. [10] In addition, synthesis of nanoparticles, [11] nanotubes, [12] or flowerlike structures [13] of GaS and Ga 2 S 3 have also been reported. [3] Thereafter,H ampden-Smith et al also reported the preparation of crystalline a-Ga 2 S 3 films by aerosol-assisted CVD from Ga(S 2 CMe) 2 Me(dmpy) or Ga(S 2 CMe) 3 (dmpy) (dmpy = 3,5-dimethylpyridine) [4] and finally, O'Brien et al described using Ga(S 2 CNMeHex) 3 to deposit a-Ga 2 S 3 films on GaAs(111)s ubstrates by low-pressure CVD [5] and ad ifferent single-source precursor (SSP), [Ga(SiPr) 2 (m-SiPr)] 2 , was used for the preparationo fh igh-quality a-Ga 2 S 3 and g-Ga 2 S 3 films by the CVD method as well.…”
Section: Introductionmentioning
confidence: 99%
“…The short ion diffusion length facilitates the diffusion and the corresponding insertion and extraction of the ions. The active materials fabricated by ALD mainly include metal oxides (e.g., SnO 2 , ZnO, TiO 2 , V 2 O 5 , Co 3 O 4 , Fe 2 O 3 , NiO, MnO x , RuO 2 ), [179][180][181][182][183][184][185][186][187] sulphides (e.g., GaS x ), [188,189] and others (e.g., LiCoO 2 , LiMn 2 O 4 , Li 4 Ti 5 O 12 , FePO 4 , LiFePO 4 ). [178] The short path lengths for ion diffusion permit the application of low Li + conductive materials, high rate performance and high energy densities.…”
Section: Deposition Of Active Filmsmentioning
confidence: 99%